EDUKASI PENCEGAHAN COVID-19 DAN SOP ADMINISTRASI DI DESA PANDANSARI LOR - Nagari, Primasa Minerva; Nurannisa, Maulyda; Sari, Syafira Artina; Khasana, Maulidatul; Zakariya, Khoirul Anam (Universitas Muhammadiyah Malang, 2021)
The problem that arises in Pandansari Lor Village is that there is no print media that explains the dangers of Covid-19. Making posters with the theme of preventing covid-19 and implementing the new normal aims to improve public education, especially the people of Pandansari Lor Village in breaking the chain of the spread of covid-19. In addition, the installation of the administrative SOP banner also makes it easier for the public to know the flow and administrative requirements at the Pandansari Lor Village Office. The implementation method is putting up posters at several crowded points which are divided into three hamlets in Pandansari Lor Village, and in each hamlet 15 posters will be placed which are distributed to strategic locations and also several tourist destinations. The result of this activity is that the community is expected to be able to increase self-awareness and always apply the existing health protocols, and the community is facilitated by the administration service flow at the Pandansari Lor Village Office.